Etude de L’efficacite d’un Belier Amortisseur - Bellefleur, S.; Amram, M.; Zinsch, L. (Canadian Acoustics, 1992)
The aim of this work was to check the efficteveness of a steel bucking-bar with two half-filled mercury pits in reducing the sound pressure level of a riveting gun. For that purpose, a sound pressure level comparison for the two kinds of bucking-bar, standard and with mercury, was realized. The effects of some parameters, like the bucking-bar applied force or the impedance of its support were investigated. The behaviour is similar to that of a band-stop filter.